Design of a spherical parallel robotic wrist mechanism (2024)
This document presents the process of design, manufacturing, and testing of a coaxial spherical parallel manipulator as the mechanism for a robotic wrist. To achieve this, a kinematic model of the mechanism was developed from which was possible to determine the best parameters to guarantee the desired performance. All together with the use of 3D printing as manufacturing method, and the development of a simulation environment and a GUI for the proper control of the device, different types of positions and movements of the mechanism were tested.